Thermoplastic matrix plates in elasto-plastic finite element analysis - Arslan, N; Çelik, M (Sage Publications Ltd, 2001)
A two-dimensional finite element computer program is developed for elasto and elasto-plastic analysis. The analysis of the semicircular and U shaped edge notched plates manufactured from steel-thermoplastic composite is made under the uniform tension loads. Isoparametric quadrilateral element with four and nine nodes is used with Lagrange polynomial as an interpolation function. Art initial stress method (modified Newton-Raphson) is used to determine elasto-plastic stresses in the finite element solution. Distribution of the plastic regions near the notch and variations of residual stresses are investigated in different orientation angles and loads for steel-thermoplastic composite plates with edge notches.
Keywords: elasto-plastic deformation; residual stress; reinforced thermoplastics; notched composite plate; finite element method